GESTIÓN DE CALIDAD PARA LA PUESTA EN VALOR DE LOS BAÑOS TERMALES DE CHURÍN EN LA PERSPECTIVA DEL DESARROLLO SOSTENIBLE - Cruz Gonzales, Niko (2013)
The investigation is entitled “Management Quality for the value of the bath thermal Churín in the perspective of Sustainable Development”. The overall objective of the research is to analyze quality to highlight the bath thermal Churín in a development perspective tourist sustainable. To meet this goal has been made a revision bibliographies approaches you mean Management of the rich tourists and has systematized the information documentary on natural conditions, the potential tourists and perceptions tourists and residents of the town on the importance of the bath springs in this town. The methodology used made it possible to review and evaluate the conditions and character tics of bath springs, ace as the valuation of its infrastructure in goods and services provided to tourists. The findings define the terms of theoretical and practical quality management on the various processes, goods and services as well as people’s participation as a necessary condition for sustainable tourism activity. The perception of tourists and residents expressed the shortcomings and limitations of the current tourism development and the need to take on political commitments to achieve improved quality of life in this town. The value of the thermal baths and construction of roads and other facilities to reach a total of S/. 21’ 641.457,00.